Studi Komparatif Sikap Ta’dzim Santri Antara Dayah Tradisional dan Modern di Aceh - Alimuddin (Tadabbur: Jurnal Peradaban Islam, 2021)
This research is motivated by the decline in morals and the increasingly rare attitude of respect for students to their teachers who are suspected of current public education institutions failing to shape the morals of their students. However, on the other hand, dayah educational institutions are still consistently producing generations of knowledge and noble character, one of which is respect. Furthermore, glorify (ta'dzim) to (parents, teachers, etc.). However, each of the traditional and modern dayahs has its way of instilling the moral values/ta'dzim attitude, and this is because the two have different learning systems/patterns. The purpose of this study was to describe the form of teaching and practice of santri ta'dzim attitudes in traditional and modern dayahs and the similarities and differences between the two. This research was conducted by field study using the descriptive qualitative method with data collection techniques in literature study, interviews, observation and documentation. The results showed that the teaching/ method of fostering ta'dzim attitudes at the Thalibul Huda and Modern Darul 'Ulum YPUI Banda Aceh schools by using reading books, lectures, advice and guidance methods, while in practice, in both dayahs they had a ta'dzim attitude to the teachers (Tengku/ustadz). or the leader of the dayah in the form of speaking or conveying something politely and courteously. In daily activities, when the teacher explains the lesson or speaks, the students listen and do not argue or show an attitude that does not please the teacher.